Genomics overrules mitochondrial DNA, siding with morphology on a controversial case of species delimitation. Issue 1900 (3rd April 2019) - Pedraza-Marrón, Carmen del R.; Silva, Raimundo; Deeds, Jonathan; Van Belleghem, Steven M.; Mastretta-Yanes, Alicia; Domínguez-Domínguez, Omar; Rivero-Vega, Rafael A.; Lutackas, Loretta; Murie, Debra; Parkyn, Daryl; Bullock, Lewis H.; Foss, Kristin; et al.
Abstract : Species delimitation is a major quest in biology and is essential for adequate management of the organismal diversity. A challenging example comprises the fish species of red snappers in the Western Atlantic. Red snappers have been traditionally recognized as two separate species based on morphology: Lutjanus campechanus (northern red snapper) and L. purpureus (southern red snapper). Recent genetic studies using mitochondrial markers, however, failed to delineate these nominal species, leading to the current lumping of the northern and southern populations into a single species ( L. campechanus ). This decision carries broad implications for conservation and management as red snappers have been commercially over-exploited across the Western Atlantic and are currently listed as vulnerable. To address this conflict, we examine genome-wide data collected throughout the range of the two species. Population genomics, phylogenetic and coalescent analyses favour the existence of two independent evolutionary lineages, a result that confirms the morphology-based delimitation scenario in agreement with conventional taxonomy. Despite finding evidence of introgression in geographically neighbouring populations in northern South America, our genomic analyses strongly support isolation and differentiation of these species, suggesting that the northern and southern red snappers should be treated as distinct taxonomic entities.